Prediction on the results of sailing boat event in 2008 Beijing Olympic Games - Wang, Z.; Jiang, S.; Jiang, Y.; Wang, J. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Considering the fuzzy and uncertain characters of the sport event results of previous Olympic Games, this paper brings forward the prediction models and methods to predict the results for different sport events by means of logarithmic, exponential, trigonometric and their derivation models. Therefore it has been obtained the optimum prediction model for every sport event. Based on the methods, this paper tests the results of track and field, diving, bicycle, horsemanship, and rowboat of 2004 Olympic Games. The results show that the accuracy exceeds 98 percents. In addition, the mentioned prediction models and methods have been employed to predict the results of sport events in 2008 Olympic Games as well as the post-validation. It is found that the models are credible to predict the rules of sport results vary with the time serial.